Modularity and innovation in complex systems - Sendil K. Ethiraj; Daniel Levinthal (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2003)
The problem of designing, coordinating, and managing complex systems has been central to the management and organizations literature. Recent writings have tended to offer modularity as, at least, a partial solution to this design problem. Two unifying themes characterize the extant literature on modularity. The first addresses the contingencies under which modular design structures are favored over integrated ones. A second theme in the literature revolves around the power of modularity wherein the focus is on the advantages that modular design structures have over their integrated counterparts. However, little attention has been paid to the problem of identifying what constitutes an appropriate modularization of a complex system. We develop a formal simulation model that allows us to carefully examine the dynamics of innovation and performance in complex systems. We show that there is an important asymmetry between the performance implications of over- and under-modularity. While excessive levels of integration can slow the pace of adaptation and can lead to premature lock-in to an inferior outcome, excessive levels of modularity can, in the limit, stymie any possibility of adaptive change. The analysis highlights an asymmetry in this trade-off, with excessively refined modules leading to cycling behavior and a lack of performance improvement. We discuss the implications of these arguments for product and organization design.
Keywords: M0; 330; modularity; complex systems; innovation; adaptation; Organisationstheorie; Modularisierung; Komplexitätsmanagement